The occurrence of endophytic fungus Phomopsis oblonga on elms in the area of southern Bohemia - M. Dvořák; D. Palovčíková; L. Jankovský (Journal of Forest Science, 2006)
The health condition of the population of elms in the region of southern Bohemiawas studied from the viewpoint of their decline, the occurrence of Dutch Elm Disease (DED) and the presence of other diseases. Of the total number of 105 elms in total 33 of them were without any symptoms of the disease or other damage. Elms regenerated quite spontaneously in the neighbourhood of mother trees and their increasing population in mixed forests is hopeful. According to macroscopic symptoms, DED was identified in 10 trees but the presence of pathogens Ophiostoma ulmi and Ophiostoma novo-ulmi was not identified in isolations. A possible reason of this observation is overgrowing the colonies by the Phomopsis oblonga mycelium. This fungus was identified in most isolations. Thus, its role requires further research.